Physiological and Biochemical Responses to Sublethal Concentrations of the Novel Pyropene Insecticide, Afidopyropen, in Whitefly Bemisia tabaci MED (Q Biotype) - Xuan Zhou; Ziyi Zhang; Huixin Zheng; Qinghe Zhang; Jingyu Gong; Chuanren Li; Ran Wang (Agronomy, 2021)
Bemisia tabaci is a devastating agricultural insect pest worldwide, and B. tabaci MED (formerly biotype ‘Q’) threatens the production of horticultural and economic crops in China as a growing number of cases of insecticide resistance have issued, highlighting the requirement for alternative methods and measures of pest management. In the present work, the toxicities of eight popular chemical agents, including the novel pyropene insecticide afidopyropen, on adults of B. tabaci MED were determined, and then physiological and biochemical responses to sublethal concentrations were confirmed. Among all tested chemical agents, afidopyropen exhibited the highest toxicity to adult whiteflies (LC50: 7.38 mg/L). The sublethal effects of afidopyropen were studied at two sublethal concentrations, LC10 (0.53 mg/L) and LC25 (1.84 mg/L), and LC25 treatment extended the duration of growth stages and reduced viabilities in the stages of nymphal, pseudopupae, and adults. The egg-laying days and eggs laid per female were also decreased significantly, as was hatchability in the LC25 treatment. Metabolic enzyme assays suggested that the sublethal effects of LC25 treatment could be ascribable to enhanced detoxification mediated by glutathione S-transferase. In summary, our findings indicate that afidopyropen can be used as a chemical agent for the management of B. tabaci MED whiteflies.